760 Investigating Theatre Cancellation Rates in a London Hospital. (19th August 2022) - Giles, R; Murray, CE; Basu, A; Dharmasekara, B; Surendran, S
Abstract: Aim: Theatre cancellations are a major source of system inefficiency, placing an unnecessary financial burden on the NHS. The aim of this audit was to investigate the reasons for cancellations in elective surgery at a London hospital and to assess the general preoperative process. Method: We undertook a retrospective audit of all elective theatre cancellations from the day surgery unit over a three-month period in 2021. 78 cancellations were identified, and their cause was investigated. Furthermore, we reviewed theatre lists over one month to calculate the proportion of cancelled procedures per specialty. Also, to gain a further understanding of the present protocol, we reviewed the current preoperative process. Results: The main reason for cancellations was patients being physiologically unfit for surgery, accounting for 28.2% of all cases. The next biggest reason for cancellation, at 16.7%, was failure to comply with COVID protocol. The specialty with the largest proportion of cancellations was General Surgery, at 17.7%. Conclusions: We believe many reasons for cancellations were avoidable. Therefore, we propose a change to the preoperative process to target multiple reasons for cancellation. We suggest a more comprehensive pre-admission phone call five days prior to surgery which includes discussions around medication compliance and changes in condition. We also suggest a set of observations and routine bloods are taken when patients come in for their COVID swab. This allows any potential cause of cancellation to be identified and rectified, or the patient could be rescheduled. This should increase efficiency of the day surgery unit.